Effect of ramosetron on QTc interval: a randomised controlled trial in patients undergoing off-pump coronary artery bypass surgery. Issue 1 (December 2015) - Kim, Tae; Cho, Youn; Lim, Chae-won; Min, Jeong; Choi, Eue-Keun; Hong, Deok; Jeon, Yunseok
Abstract Background Ramosetron is a relatively new 5-hydroxytryptamine three receptor antagonist with higher binding affinity and more prolonged duration of action compared to ondansetron. The present study was performed to evaluate the effects of ramosetron on QTc interval and possible cardiovascular adverse effects in patients undergoing cardiac surgery. Method A total of 114 patients who underwent off-pump coronary artery bypass surgery were enrolled in this randomised placebo-controlled trial. Patients were allocated into two groups that received intravenous injection of 0.3 mg ramosetron or normal saline during induction of anaesthesia. QTc intervals were measured before the operation, intraoperatively (0, 1, 2, 3, 5, 10, 15, 30, 45, 60, 90, 120, and 240 min after injection of ramosetron or normal saline), at the end of the operation, and on postoperative day 1. Results There were no differences in mean QTc interval between groups at every time point. However, maximal change in QTc interval during surgery was higher in the ramosetron group than the placebo group (25.1 ± 22.0 vs. 17.5 ± 14.5 ms, 95 % CI 0.34–14.78, P  = 0.040). Also, there were more patients with a QTc interval increase of > 60 ms in the ramosetron group (5 vs. 0, 95 % CI 1.6–18.0, P  = 0.021). There were no significant differences in cardiovascular complications. Conclusions Ramosetron administered during induction of anaesthesia may affect maximal change in QTc interval during off-pump coronary artery bypass surgery. Ramosetron should be used with caution in high risk patients for developing Torsades de Pointes. Trial registration ClinicalTrials.gov NCT02139241. Registered November 12, 2013